Foaming Properties of Sesame Seed Protein Hydrolyzates - Sreedevi, S.; Balasubramanian, V.; Sivasankar, B. (Asian Journal of Chemistry, 2010)
Sesame seed protein isolates have been hydrolyzed using enzyme trypsin. The degree of hydrolysis (6, 8 and 10 %) was determined by the pH-stat method. The foaming capacity and foam stability was determined by the electrical conductivity method. The effect of degree of hydrolysis and pH on the foaming properties were also studied.